Manufacture and characterization of lightweight sand-plastic composites made of plastic waste and sand: Effect of sand types - Salih Mekideche; Mansour Rokbi; Zine El Abidine Rahmouni; Resego Phiri; Sanjay Mavinkere Rangappa; Suchart Siengchin (International Journal of Lightweight Materials and Manufacture)
Over the past decade, many types of waste have been exploited as feedstocks in different industries. Recycled plastics are among the waste sought for several civil engineering applications. In this work, various plastic-bonded sand composites based on polypropylene waste and silica sand were produced to serve as building materials in many construction applications. Many tests and analysis were carried out in this investigation. First of all, two initial used compounds (waste PP and various silica sand) were analyzed by using ATR-FTIR, XRF, and grain size distribution. In the second time, the different plastic-bonded sand composites were analyzed by using ATR-FTIR to assess their composition. On the other hand, mechanical, and physical tests such as three-point flexural strength, compressive strength, water absorption, and optical observation were applied on different produced composite samples, then the results were examined and analyzed. The results showed that the developed composites exhibit commendable mechanical properties, especially flexural and compression resistance, and minimal water absorption. It is worth noting that the plastic-bonded sand containing Khobana sand showed the highest flexural and compressive strength at 11.56 ± 0.36 and 26.19 ± 0.27 MPa, respectively, along with the lowest water absorption rate of 0.46%. This study confirms its contribution to enhancing sustainability and promoting the principles of the circular economy.